The Mosquito Microbiome: Implications for Pathogen Transmission and Pharmaceutical Vector Control Strategies - Dr. Kiran Bala Bhuyan; Dr. Tanmay Ghosh; Dr. Puspanjali Maharana; Gnanamoorthy Kumaran; Dr. Ram Kumar; Dr.Deepalakshmi (The Bioscan, 2025)
Mosquito-borne diseases such as malaria, dengue, Zika, chikungunya, and yellow fever continue to pose major public health challenges worldwide. Recent advances in molecular biology and high-throughput sequencing have revealed that mosquitoes harbor diverse microbial communities collectively referred to as the mosquito microbiome. These microorganisms—including bacteria, fungi, viruses, and protozoa—play crucial roles in mosquito development, metabolism, immunity, and vector competence. Increasing evidence demonstrates that the microbiome can significantly influence pathogen acquisition, replication, and transmission within mosquito vectors. Consequently, microbiome-based interventions have emerged as innovative alternatives or complements to conventional chemical insecticides. This review provides a comprehensive synthesis of current knowledge on mosquito microbiome composition, host–microbe–pathogen interactions, immune modulation, and their implications for pathogen transmission. Furthermore, emerging pharmaceutical and biotechnological vector control strategies, such as Wolbachia-based approaches, paratransgenesis, microbial biopesticides, and microbiome manipulation, are critically evaluated. Challenges, ethical considerations, and future research directions are also discussed, highlighting the potential of microbiome-centered strategies for sustainable vector control. KEYWORDS Mosquito microbiome; vector competence; arboviruses; malaria; Wolbachia; paratransgenesis; pharmaceutical vector control; microbial biopesticides